Innovation Forms and Firm Export Performance: Empirical Evidence from ECA Countries - Andrzej Cieślik; Jan Jakub Michałek (Entrepreneurial Business and Economics Review)
Objective: The main objective of this paper is to verify empirically the relationship between various forms of innovation and export performance of firms from European and Central Asian (ECA) countries.